The impact of land consolidation on rapeseed cost efficiency in China: policy implications for sustainable land use and food security - Zhang, Qing; Ye, Feng; Razzaq, Amar; Feng, Zhongchao; Liu, Yi (Frontiers in Sustainable Food Systems, 2024)
The relationship between farm size expansion and efficiency is a key topic in agricultural economics, especially for achieving sustainable land use and food security. While existing literature focuses on land productivity, technical efficiency, and total factor productivity, the link between farm size and cost efficiency remains less explored. Cost efficiency is a critical indicator of production effectiveness and directly impacts agricultural sustainability and food security. This paper analyzes how farm size expansion affects the cost efficiency of Chinese rapeseed production, with a particular emphasis on sustainable agricultural production and food security. Our findings indicate an average cost efficiency of 0.740 for rapeseed in China, suggesting potential for improvement. We observe an inverted U-shaped relationship between farm size and rapeseed cost efficiency, with variations based on regional and topographic conditions. Optimal rapeseed farm size is between 10 and 30 mu in eastern and central China, and smaller than 10 mu in western China. Interestingly, in central China and plains regions, larger farm sizes have a less negative impact on cost efficiency. Finally, increasing plot size positively moderates the relationship between farm size and rapeseed cost efficiency, suggesting benefits from expanding both plot and farm sizes simultaneously. These findings provide empirical evidence to inform policy decisions related to sustainable land use, costefficient agriculture, and food security.